2012
DOI: 10.3390/md10092089
|View full text |Cite
|
Sign up to set email alerts
|

Application of HPLC-NMR in the Identification of Plocamenone and Isoplocamenone from the Marine Red Alga Plocamium angustum

Abstract: A combination of on-line HPLC-NMR and off-line chemical investigations has resulted in the identification of the previously reported polyhalogenated monoterpene plocamenone, together with the new structural analogue isoplocamenone from the crude extract of the marine alga Plocamium angustum. On-flow and stop-flow HPLC-NMR analyses (including the acquisition of WET 2D NMR spectra) rapidly assisted in the identification of the major component plocamenone and in the partial identification of its unstable double b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 45 publications
4
30
0
Order By: Relevance
“…Chiralities were established by comparison of experimental NMR shis and CD spectra with results from DFT calculations. 575 Syntheses of plocamenone and isoplocamenone have conrmed their structures 576 and established their absolute congurations. 577 Total syntheses of the proposed structures of microcladallenes A, B and C 578 conrmed the structures of A and B but indicated that microcladallene C could not be correct.…”
Section: Brown Algaementioning
confidence: 99%
“…Chiralities were established by comparison of experimental NMR shis and CD spectra with results from DFT calculations. 575 Syntheses of plocamenone and isoplocamenone have conrmed their structures 576 and established their absolute congurations. 577 Total syntheses of the proposed structures of microcladallenes A, B and C 578 conrmed the structures of A and B but indicated that microcladallene C could not be correct.…”
Section: Brown Algaementioning
confidence: 99%
“…Green algae and red algae appear to be less studied, both in a natural product capacity, and as a source of crude extract bioactivity, yielding 9 and 5 species that display crude extract or pure compound bioactivity, respectively. Many studies have contributed to the isolation and identification of the large number of compounds that have been chemically profiled and discovered utilising hyphenated techniques such as HPLC-NMR and HPLC-MS [57,62,91,118,122,133,157,189]. This has expedited the process of dereplication and allowed for a more efficient pathway to the isolation and characterization of bioactive components present in crude extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Plocamenone was subsequently tested for cytotoxicity against P388 tumour cells showing promising IC 50 values of 157.5 ng/mL and >97.5 ng/mL when derived from two separate samples. This same study assayed a mixture of plocamenone and isoplocamenone which achieved an IC 50 value of >97.5 ng/mL, but isoplocamenone was unable to be assayed individually due to its instability [122]. The alga P. costatum was studied in a phytochemical capacity as early as 1976 when two separate papers were published wherein both independently reported the identification of halogenated monoterpenes [123,124].…”
Section: Halogenated Monoterpenesmentioning
confidence: 99%
“…The use of HPLC-NMR for the identification and isolation of plocamenone and isoplocamenone from the marine red alga Plocamium angustum has recently been reported (Timmers et al, 2012). Within the past three decades, LC, a robust separation technique, has been coupled to NMR spectroscopy for determination of structures of unknown complex molecules.…”
Section: Lc-nmrmentioning
confidence: 99%